Water-soluble fluorosilane supplemented with fumed silica as admixture for producing hydrophobic concrete: Effects on cement hydration, mechanical properties and water protection properties - Jorge González-Coneo; Rafael Zarzuela; Manuel Luna; María J. Mosquera (Developments in the Built Environment, 2024)
Hydrophobic admixtures protect concrete from water-related degradation, although they may have negative effects over cement hydration, mechanical properties and have low miscibility with water. Aiming to overcome these drawbacks, this work studies the properties of concretes containing admixtures based on a water-soluble fluoroalkylsilane and fumed silica to densify the structure. The effects of the admixture were evaluated in terms of hydrophobic, mechanical and chemical properties.The admixture decreased capillary absorption by over 70% while also increasing the internal cohesion, despite an increased porosity. Raman and XRD analysis indicated it promoted the consumption of C3S and the formation of portlandite and C–S–H gels with higher silicon content, compensating the effect of porosity on the concrete resistance. Incorporation of fumed silica in the admixture delayed the early development of hydrated phases, but after full curing promoted a more compact structure of the cement matrix, decreasing water absorption rate and improving mechanical properties.